Shrinking cities: Effects on urban ecology and challenges for urban development. 2nd, rev. ed. - (:unkn) unknown (Lang, 2014)
Cities in industrialised countries have grown over time, yet shrinkage of cities occurs in many regions. This process has many impacts on urban ecology, which can be observed on urban brownfield sites in particular. The integration of these sites with sustainable urban development must be managed. This presents new challenges for urban planners. The first chapters give an overview of urban ecology concepts and how research in this field is affected by urban shrinkage. The following sections are concerned with botanical aspects of shrinking cities, perception of nature in the context of shrinkage and discussion of aspects of urban planning with reference to several regional examples. The book concludes with a study of urban shrinkage during the life cycles of city archetypes.
Keywords: Stadtentwicklungsplanung; Schrumpfung; Stadtökologie; Brachfläche; Stadtsanierung; Stadterneuerung; Verdichtung; Stadtklima; Grünfläche; Straßenbahn; Stadtumbau; Nachverdichtung; Nachhaltigkeit